Analisis Quality of Service Untuk Memonitoring Kondisi Topologi Jaringan X - Ratih Nindyasari; Muhammad Imam Ghozali (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
To supporting daily activities, humans are dependent on the technology. All these activities can take place well if there is a technology that can connect with each other. This technology is called the internet network. For that we need a special management that can regulate the condition of a network to have good quality. Because network quality will affect the productivity of a person. For this reason, we need a standard for measuring network quality known as Quality Of Service (QoS) to maintain the quality of Qos services by monitoring network traffic. In this study, an internet network service on an X topology will be tested. The result is that using QoS analysis produces a number of delays in good categories, the number of packet loss in good categories in scenarios 1 and 2, and the moderate category in scenario 3 and the number low inputput so that it has a good category in scenarios 1, 2 and 3. Based on this condition it can draw the conclusion that the number of delays is directly proportional to the number of packet loss, so that the higher the delay, the more the number of packet loss. While the number of delay and packet loss is inversely proportional to the amount of input in a network condition. So if the lower delay and packet loss, the resulting output will be higher. Keywords: QoS Analysis, Network Topology, Delay, Packet Loss, Troughtput